News agenda and representation of childhood and adolescence in Chilean television newscasts - Condeza Dall´Orso, Rayén (2022)
This article studies the content of the information on childhood and adolescence broadcast daily in the main television newscasts in Chile during prime time. It starts from the assumption that the news discourse is one of the central axes of its sociocultural construction, by putting into circulation different representations and imaginaries about these groups through the media. To determine the news topics about childhood and adolescence, the presence of stereotypes and the preferential informative treatment of television channels, we conducted a quantitative analysis between March and June 2020, finding 109 videos. The results show a news agenda concentrated on four main themes: abuse (28.4%), children's rights (24.8%), lawbreakers (22%) and participation in demonstrations (14.7%). 36% of the news presents stereotypes. When analyzing the correspondence by television channel, it is observed that the news agenda on childhood and adolescence of some newscasts mobilizes negative stereotypes with greater frequency. Because these TV programs continue to be the most consumed daily by the population in Chile to know about current events, this line of research may contribute to a greater awareness of the relevance that news frameworks, thematic diversity and an ethical perspective have in the public opinion process.